Neurosensory feedback and its role in restorative dentistry enhancing patient comfort - Alakkad, Tarik Mohammed Ali; Abdulmajeed, Zeyad Waleed; Alqahtani, Omar Saeed; Alshehri, Ghadah Mohammed; Alqessayer, Nuaif Hussain; Alotaibi, Mohammed Bander; Alqahtani, Hazzaa Hassan; Almaliky, Ghida Saeed; Balbaid, Shomous Zuhair; Almakrami, Ali Mohammed; Alshahrani, Norah Ahmed (International Journal Of Community Medicine And Public Health, 2025)
Neurosensory feedback plays a critical role in restorative dentistry, directly influencing the precision of procedures and the comfort experienced by patients. It involves the transmission of sensory signals from the oral tissues to the brain, enabling clinicians to adapt techniques based on patient-specific responses. This process is essential in minimizing procedural discomfort and ensuring functional outcomes, particularly in complex interventions such as dental implants, crowns and endodontic treatments. Mechanoreceptors within the periodontal ligament and pulp provide real-time feedback, guiding adjustments to occlusion, alignment and prosthetic fit. Challenges arise due to variability in neurosensory responses influenced by factors like age, prior trauma and systemic conditions. The absence of natural sensory interfaces, such as the periodontal ligament in dental implants, further complicates the restoration process. While Osseo perception compensates to an extent, its limitations often affect the fine-tuning of occlusion and tactile control. Innovations in biomaterials and surgical techniques have addressed some of these concerns by enhancing compatibility and preserving nerve pathways. However, inflammatory reactions and postoperative sensory disturbances remain common complications. Emerging technologies, such as cone-beam computed tomography and tactile sensors, offer improved diagnostic and therapeutic capabilities, aiding in the management of neurosensory impairments. Despite their promise, accessibility and cost continue to pose significant barriers, limiting widespread adoption. Research into biocompatible materials and neural regeneration strategies holds potential for further advancing restorative dentistry. Emphasizing patient-centered care through preoperative counseling and meticulous technique adaptation can enhance satisfaction and comfort. Overcoming the limitations of neurosensory integration requires a multidisciplinary approach involving clinicians, researchers and material scientists to ensure that restorative procedures achieve both functional and sensory excellence while prioritizing patient well-being.